2019
DOI: 10.3390/ijms20061325
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone Expression in Endometrial Cancer Tissue

Abstract: Anti-Müllerian hormone (AMH) is a commonly known factor secreted by Sertoli cells, responsible for regression of the Müllerian ducts in male fetuses. AMH has also other functions in humans. In vivo and in vitro studies have shown that AMH inhibits cell cycle and induces apoptosis in cancers with AMH receptors. The aim of the study was to assess whether the tissue of pre-cancerous states of endometrium (PCS) and various histopathologic types of endometrial cancer (EC) exhibit the presence of AMH. We aimed to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Little is known about AMH expression in the oviduct and endometrium in all species. However, a previous study utilizing immunohistochemistry detected AMH expression in the human endometrium (Wang, Dicken, Lustbader, & Tortoriello, 2009) and human endometrial cancer tissue (Gowkielewicz et al, 2019). Recently, AMHR2 expression was discovered in healthy human endometrial tissues (Kim et al., 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Little is known about AMH expression in the oviduct and endometrium in all species. However, a previous study utilizing immunohistochemistry detected AMH expression in the human endometrium (Wang, Dicken, Lustbader, & Tortoriello, 2009) and human endometrial cancer tissue (Gowkielewicz et al, 2019). Recently, AMHR2 expression was discovered in healthy human endometrial tissues (Kim et al., 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, to our knowledge, there is no information on AMH concentration in tumors. Recently, Gowkielewic et al analyzed AMH expression in 232 endometrial tumors by immunohistochemistry, and found that it was expressed in 23 samples 36 . However, the authors did not analyze AMH potential role in tumor development 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, analyses revealed that the period of estrogen activity has no effect on differences in AMHRII presence. Though, it was noticed that a period of hormonal activity longer than 40 years has a positive effect on the presence of AMH into endometrial cancer tissue and thus probably reduces the malignancy and spread of the cancer [ 19 ]. The above facts can describe the mechanisms controlling AMHRII expression in EC tissues as independent from sex hormone activity.…”
Section: Discussionmentioning
confidence: 99%
“…Case history reviews were collected for all patients in order to record demographic details and tumor characteristics, including comorbidities and survival outcomes. Biopsy samples from the affected area were processed as previously described [ 19 ]. Briefly, samples were preserved in 4% buffered formaldehyde in the form of a ready-to-use phosphate-buffered solution (Chempur, Poland) immediately after surgical removal of tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation